2021
DOI: 10.1002/lno.11705
|View full text |Cite
|
Sign up to set email alerts
|

Diatom response to alterations in upwelling and nutrient dynamics associated with climate forcing in the California Current System

Abstract: The California Current System displays a strong seasonal cycle in water properties, circulation, and biological production. Interactions of the alongshore current with coastal and topographic features lead to high spatial variability forced by seasonal winds that displace surface coastal water offshore. This process also supplies nutrients to the euphotic zone by Ekman transport and eventually supports phytoplankton blooms typically dominated by diatoms. Here, we investigate the relationship between biogenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…However, the potential for Fe‐limitation in a normally Fe‐replete region was shown during the same cruise in a moderate shelf region off Cape Blanco, Oregon, just 300 km north (Till et al 2019). It is also worth noting that while Si has not typically been thought to be a limiting nutrient for diatoms in the NE Pacific (Wilson and Qiu 2008), recent work, including analyses from this cruise, have found evidence of Si limitation in the California Current System (McNair et al 2018; Closset et al 2021). The Si:N ratios from eddy I suggest that eventual Si limitation was possible during macronutrient drawdown and that non‐siliceous phytoplankton may also have been important contributors to the community, which our analyses would not capture.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the potential for Fe‐limitation in a normally Fe‐replete region was shown during the same cruise in a moderate shelf region off Cape Blanco, Oregon, just 300 km north (Till et al 2019). It is also worth noting that while Si has not typically been thought to be a limiting nutrient for diatoms in the NE Pacific (Wilson and Qiu 2008), recent work, including analyses from this cruise, have found evidence of Si limitation in the California Current System (McNair et al 2018; Closset et al 2021). The Si:N ratios from eddy I suggest that eventual Si limitation was possible during macronutrient drawdown and that non‐siliceous phytoplankton may also have been important contributors to the community, which our analyses would not capture.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the SST is elevated at these three stations compared to the other eddy I stations, suggesting upwelling did not occur recently. Previous work has suggested it takes up to 3 d of relaxation post upwelling for diatom communities to fully develop in response to California Current System upwelling events (Wilkerson et al 2006; Closset et al 2021). The elevated chlorophyll, reduced nutrient concentrations, and grouping of diatom communities at Stas.…”
Section: Discussionmentioning
confidence: 99%
“…The CalCOFI time series of flow cytometry‐based phytoplankton community composition (Nagarkar et al 2021) also indicated that warm periods, when we expect greater f w values, are correlated with a phytoplankton community of smaller cells including autotrophic cyanobacteria. Another recent study observed lower biogenic silica to Chl a ratios during the period of the warm anomaly, suggesting a decrease in the abundance of siliceous phytoplankton at that time (Closset et al 2021). Taken together, positive Si ex values coincident with higher f w do not mean that iron limitation was unimportant, rather it could mean that the influence of iron limitation was not recorded by Si ex due to the absence of diatoms.…”
Section: Discussionmentioning
confidence: 97%
“…Characterized by equatorward wind patterns that result in a net offshore transport of surface water and the upwelling of cold nutrient‐rich water from below (Huyer 1983), these regions provide for extensive phytoplankton blooms that not only support the local food web but also mediate the flux of carbon into the deep ocean (Capone and Hutchins 2013). The California Current system (CCS), one such EBUC, is particular in its irregular bathymetry and seasonality, where the frequency of upwelling is enhanced more often during the spring and summer (Closset et al 2021). The unusual qualities of the CCS are furthermore pronounced by its Fe limitation mosaic (Hutchins et al 1998; Bruland et al 2001), in which regions with wide and shallow continental shelves are mostly considered Fe‐replete, while those with narrow and deeper continental shelves have been found to experience Fe limitation of phytoplankton growth (Bruland et al 2001).…”
Section: Figmentioning
confidence: 99%